the busness. - Hosking, Patrick (New Statesman, 2005)
Presents the authors view's on Internet gambling, with particular focus on the success of the company PartyGaming. Introduction of PartyGaming to the London Stock Exchange; Review of the company's history and its creation by former pornography entrepreneur Ruth Parasol and computer programmer Anurag Dikshit; Statistics relating to the company's overall value.